2016
DOI: 10.3390/agronomy6020031
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Better Understanding of Agronomic Efficiency of Nitrogen: Assessment and Improvement Strategies

Abstract: Agronomic N-use efficiency is the basis for economic and environmental efficiency, and an effective agro-ecosystem management practice, improving nutrient use efficiency, is a crucial challenge for a more sustainable production of horticultural, industrial and cereal crops. However, discrepancy between theory and practice still exists, coming from large gaps in knowledge on net-N immobilization/mineralization rates in agro-ecosystems, as well as on the effects of indigenous and applied N to crop response. A mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 8 publications
0
21
0
Order By: Relevance
“…The AE is an integrated index of two nutrient efficiency indices; recovery efficiency and physiological efficiency ( Ladha et al., 2005 ). For example AE-N is the bases for both economic and environmental efficiencies ( Montemurro and Diacono, 2016 ). Therefore, we calculated AE-N, AE-P, and AE-K using the equation below as in Ladha et al.…”
Section: Methodsmentioning
confidence: 99%
“…The AE is an integrated index of two nutrient efficiency indices; recovery efficiency and physiological efficiency ( Ladha et al., 2005 ). For example AE-N is the bases for both economic and environmental efficiencies ( Montemurro and Diacono, 2016 ). Therefore, we calculated AE-N, AE-P, and AE-K using the equation below as in Ladha et al.…”
Section: Methodsmentioning
confidence: 99%
“…Nitrogen is a key limiting element for plant growth, which is also the most complex one considering all of the potential forms and processes in its cycle (Montemurro and Diacono, 2016). It is strongly involved in all of the plant metabolic processes and its rate of uptake and partition is largely determined by supply and demand during the various stages of plant growth (Delogu et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies carried out around the world and in different environments, have shown that between 50 and 70% of the total N applied to the soil, is lost as a result of runoff, denitrification, volatilization and leaching (Montemurro and Diacono, 2016). This macroelement, is considered a potential environmental contaminant, and therefore, the efficiency (NUE) of its rational use, is fundamental for agricultural sustainability and natural environmental conservation (Yasuor et al, 2013;Mascleaux-Daubresse et al, 2010).…”
Section: Introductionmentioning
confidence: 99%